2017
DOI: 10.25073/2525-2445/vnufs.4207
|View full text |Cite
|
Sign up to set email alerts
|

World Englishes From a Holistic View and Considerations on English Education in Vietnam

Abstract: The development of English as the mutual language among ASEAN since 2008 and the formation of ASEAN Economic Community since 2015 have set milestones in the social and educational development of each country in this organisation. In English education in Vietnam, understanding the diversity of Englishes in the organisation has become an important task. This article aims to present a holistic view of World Englishes (WE) in research generally and in relation to English education in Vietnam particularly by illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…WEs in Vietnam can be traced back to its Doi Moi, or Open Door, policy, which has attracted businesspeople and investors who use English as a lingua franca to the country. Since the policy's initiation in 1986, English varieties have caught increasing attention (T. H. Tran & Ngo, 2017), and communicative competence in WEs is a must at work (T. N. Nguyen, 2017). It is understood that exposure to English varieties would better prepare students for real‐life communication (Ho & T. H. Nguyen, 2019).…”
Section: World Englishes and Teaching English Speakingmentioning
confidence: 99%
See 2 more Smart Citations
“…WEs in Vietnam can be traced back to its Doi Moi, or Open Door, policy, which has attracted businesspeople and investors who use English as a lingua franca to the country. Since the policy's initiation in 1986, English varieties have caught increasing attention (T. H. Tran & Ngo, 2017), and communicative competence in WEs is a must at work (T. N. Nguyen, 2017). It is understood that exposure to English varieties would better prepare students for real‐life communication (Ho & T. H. Nguyen, 2019).…”
Section: World Englishes and Teaching English Speakingmentioning
confidence: 99%
“…More importantly, both strategies can expose students to English varieties, depending on their own choice. However, in my design of learning materials, English varieties from the so‐called inner circle (countries where English is the first language among the general population) were used, owing to their predominance in English classrooms and materials in Vietnam (T. H. Tran & Ngo, 2017; P. M. Tran & Tanemura, 2020). Nevertheless, my modification of students’ oral production did not follow a nativist approach.…”
Section: World Englishes and Teaching English Speakingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also impossible for teachers to create interactive and interesting activities due to the time constraint of the program (Trinh & Mai, 2019). In addition, the time commitment to the job of the majority of English teachers is often low (Hoang, 2013). Nguyen et al (2015) found that there were still many negative factors hindering the efficacy of General English teaching and learning, including insufficient time for English courses, lack of speaking component in tests and examinations and large class sizes.…”
Section: General English Programs For University Students In Vietnam:...mentioning
confidence: 99%
“…Upon the effects of ongoing globalization worldwide, the need for the cultivation of English as a global language has been rising, especially when it is believed that undergraduate students should enter the 21 st century's workforce with the 4Cs (Critical thinking, Collaboration, Creativity, and Communication) (Halvorsen, 2018). As commonly recognized as a lingua franca, English plays a significant role in the promotion of the process of globalization and internationalization (Altbach & Knight, 2007;Duong & Chua, 2016) occurring in most of the world's corners, including developing nations (Hoang, 2013; Q. A.…”
Section: Introductionmentioning
confidence: 99%